HUBUNGAN PENGETAHUAN DENGAN TERJADINYA SPRAIN DAN STRAIN PADA PEMAIN SEPAK BOLA PERSIBO 1949 - AZIZAH, FIDROTIN; MAFTHUKHIN, AHMAD (AKADEMI KESEHATAN RAJEKWESI BOJONEGORO, 2016)
ABSTRACT Sprain and sprain is a form of injury to the musculoskeletal system. Soccer player is a high risk of sprains and strains experienced events. Lack of knowledge in the handling of influential players sprain and strain. The purpose of this study identify